In the context of supply chain management, the risk assessment method - Umang Jindal (Innovative Research Thoughts, 2021)
The implementation of efficient risk management in a company's supply chain is very necessary for the company to achieve success. It is the purpose of this article to provide a comprehensive analysis of the prior research on risk assessment methodologies that have been used in supply chain management studies. In addition to highlighting the necessity of risk management in supply chain management, this article provides an analysis of the several ways that have been used in order to identify, evaluate, and manage risks. As an additional point of interest, the article offers examples of how these tactics have been put into practise. Additionally, in the last part of the study, we provide some suggestions for additional research that should be conducted in this category.